Second Brazilian consensus on the management of ulcerative colitis in adults: a consensus of the Brazilian Organization for Crohn’s Disease and Colitis (GEDIIB) - Baima, Júlio Pinheiro [UNESP]; Imbrizi, Marcello; Andrade, Adriana Ribas; Chebli, Liliane Andrade; Argollo, Marjorie Costa; Queiroz, Natália Sousa Freitas; De Azevedo, Matheus Freitas Cardoso [UNESP]; Vieira, Andrea; Costa, Marcia Henriques De Magalhães; Fróes, Renata de Sá Brito; Cancela E Penna, Francisco Guilherme; Quaresma, Abel Botelho; et al. (FapUNIFESP (SciELO), 2022)
Background – Inflammatory bowel diseases are immune-mediated disorders that include Crohn’s disease (CD) and ulcerative colitis (UC). UC is a progressive disease that affects the colorectal mucosa causing debilitating symptoms leading to high morbidity and work disability. As a consequence of chronic colonic inflammation, UC is also associated with an increased risk of colorectal cancer. Objective – This consensus aims to provide guidance on the most effective medical management of adult patients with UC. Methods – A consensus statement was developed by stakeholders representing Brazilian gastroenterologists and colorectal surgeons (Brazilian Organization for Crohn’s Disease and Colitis [GEDIIB]). A systematic review including the most recent evidence was conducted to support the recommendations and statements. All recommendations/statements were endorsed using a modified Delphi Panel by the stakeholders/experts in inflammatory bowel disease with at least 80% or greater consensus. Results and conclusion – The medical recommendations (pharmacological and non-pharmacological) were mapped according to the stage of treatment and severity of the disease onto three domains: management and treatment (drug and surgical interventions), criteria for evaluating the effectiveness of medical treatment, and follow-up/ patient monitoring after initial treatment. The consensus targeted general practitioners, gastroenterologists and surgeons who manage patients with UC, and supports decision-making processes by health insurance companies, regulatory agencies, health institutional leaders, and administrators.
Segundo Consenso Brasileiro no manejo da retocolite ulcerativa em adultos: um consenso da Organização Brasileira para Doença de Crohn e Colite (GEDIIB)
Keywords: adults; Colitis, ulcerative; disease management; drug therapy; inflammatory bowel diseases